6(b+4)=0

Simple and best practice solution for 6(b+4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(b+4)=0 equation:


Simplifying
6(b + 4) = 0

Reorder the terms:
6(4 + b) = 0
(4 * 6 + b * 6) = 0
(24 + 6b) = 0

Solving
24 + 6b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-24' to each side of the equation.
24 + -24 + 6b = 0 + -24

Combine like terms: 24 + -24 = 0
0 + 6b = 0 + -24
6b = 0 + -24

Combine like terms: 0 + -24 = -24
6b = -24

Divide each side by '6'.
b = -4

Simplifying
b = -4

See similar equations:

| -9(6+u)=2u-10 | | 132=12(n+9) | | -8x+4(1+5x)=-6-14 | | 1/3x+2=1/2x+3 | | 2x^2+22x+121= | | 25x=1.2 | | 4x+7y=54 | | 3+9q=4+8q | | 16-r=16 | | 35r+500= | | 5x-17=133 | | 2(x-4.5)=-2.5+x | | 1.5(n-4.5)=13 | | 6n-2(n+1)=26+n | | 2x-2y+5y=x-4 | | 24+x=41 | | 6(p-7)-5p+15+(3p+2)4= | | 10b+2=4b+20 | | 14x-9y=102 | | 13v+2-11+5v= | | 2x+-2y=6 | | M+8=120 | | 2=0.4 | | -2(4+3x)+7=6(x+1) | | -14x+9y=46 | | 7/2a-5/4=1/a | | 2(x-1)=4(x+2) | | 4p+7=13 | | 6x+4y=-2 | | 4p+7= | | .4y=30 | | 3x+5y=54 |

Equations solver categories